Study of shoreline changes using Landsat Satellite Imagery in Tanjung Tengah and Saloloang Villages, Penajam District - Pepliani, Fera; Adnan, Adnan; Kusumaningrum , Widya (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
The coastal areas of Tanjung Tengah and Saloloang sub-districts that used as ecotourism, this research needed to determine changes in the coastline at these locations. The study aims to determine the shift of the coastline along with the extent of abrasion and accretion for 15 years on the coast in Tanjung Tengah and Saloloang Villages, Penajam District, Penajam Paser Utara Regency. The study was conducted from October 2023 to November 2023. The method used is the Digital Shoreline Analysis System (DSAS) analysis using Landsat 7 ETM and Landsat 8 OLI satellite imagery obtained from the USGS site. The results of the study showed that during the period 2009 - 2023 along the coastal areas of Tanjung Tengah and Saloloang Villages, was greater accretion than abrasion, period 2009-2015 the coast experienced a shift towards the sea (Accretion) reaching 311.95 meters. Then experienced a retreat towards the land reaching 267.11 meters from the period 2015-2023. The total area of ​​the area experiencing accretion and abrasion respectively is 81.42 ha and 41.68 ha.